1989
DOI: 10.1093/jnci/81.5.370
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of 13q Abnormalities Among 203 Patients With Retinoblastoma

Abstract: We studied peripheral blood lymphocyte karyotypes of 203 patients with retinoblastoma. Twelve (5.9%) had a constitutional chromosomal abnormality involving 13q, of whom six had unilateral and six had bilateral disease. Two patients had mosaic deletions, eight had nonmosaic deletions, one had a de novo translocation, and one had a 13q14 deletion and a de novo direct insertion (10;6). Of the total, 4.9% of unilateral and 7.5% of bilateral patients had 13q abnormalities. None of 19 familial retinoblastoma patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0

Year Published

1991
1991
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(48 citation statements)
references
References 0 publications
1
47
0
Order By: Relevance
“…The vast majority of occurrences of Down syndrome are sporadic. Three quarters of patients with genetic retinoblastoma (Bunin et al, 1989;Sanders et al, 1988) and 89% of bilateral Wilms' tumour patients (Breslow et al, 1988) occur in families with no other members affected. One-half of neurofibromatosis cases are the result of new mutations (Crowe et al, 1956) and as average family size becomes smaller, the majority of new cases of recessive disease will be isolated as well.…”
Section: Resultsmentioning
confidence: 99%
“…The vast majority of occurrences of Down syndrome are sporadic. Three quarters of patients with genetic retinoblastoma (Bunin et al, 1989;Sanders et al, 1988) and 89% of bilateral Wilms' tumour patients (Breslow et al, 1988) occur in families with no other members affected. One-half of neurofibromatosis cases are the result of new mutations (Crowe et al, 1956) and as average family size becomes smaller, the majority of new cases of recessive disease will be isolated as well.…”
Section: Resultsmentioning
confidence: 99%
“…2 In a patient with a deletion, second mutations that lead to homo-or hemizygosity, such as mitotic recombination or non-disjunction, will result in homozygous loss of all genes within the deleted region. If a patient's deletion contains a gene essential for basic cellular functions, fewer tumor foci will develop because only those second mutations will trigger tumor formation that leave the single copy of this gene intact.…”
Section: Discussionmentioning
confidence: 99%
“…1 It has been reported that the proportion of patients with unilateral Rb in carriers of 13q deletions is higher compared with patients with intragenic loss-of-function mutations. [1][2][3] In addition to Rb, patients with a 13q deletion involving the region 13q14.2 often present with pleiotropic features. On the basis of karyotype-phenotype associations, a classification for patients with a 13q deletion with and without Rb was proposed.…”
Section: Introductionmentioning
confidence: 99%
“…There is no difference in incidence according to gender or race. All cases are caused by inactivation of a tumour suppressor gene (RB) and in all cases of bilateral retinoblastoma and 15% of unilateral retinoblastoma cases the disease is due to a germ line mutation (Bunin et al 1989;Smith & O'Brien 1996;Classon & Harlow 2002).…”
Section: Retinoblastomamentioning
confidence: 99%